“You do need each member of the team to bring that next piece of the puzzle”: Allied health professionals’ experience of interprofessional complex care in hospital settings - Felice Borghmans; Venesser Fernandes; Stella Laletas; Harvey Newnham (PLoS ONE, 2025)
This study explores the experiences of allied health professionals who work in interprofessional hospital complex care teams. The aim of the study was to identify factors influential to meaningful clinician experiences in these contexts. Increase in interprofessional complex care in hospital settings reflects rising population health complexity. Furthermore, growth in these models coincides with a heightened focus on health system efficiency due to rising healthcare costs, resource constraints, and health workforce shortfalls. Combined, these issues constitute a ‘wicked problem’. However, research exploring the experiences of clinicians working under these conditions is limited, exposing the knowledge gap of interest to this study. Using a qualitative approach, in-depth interviews were conducted with allied health professionals engaged in hospital-based interprofessional complex care, and their narratives were analysed according to the conceptual framework of complex adaptive phenomenology. The study identified four interconnected themes: workplace culture and leadership, interprofessional practice, healthcare ethics, and the ambiguity of complex care. Furthermore, the notion of ‘empowerment of self and others’ was a continuous thread throughout, which appeared essential to effective interprofessional practice. The study showed how the clinician experience provides a window to the functioning of a healthcare system and the bearing of experience on healthcare efficiency and sustainability. Recommendations include developing a more balanced approach to ‘efficiency’ in policy settings, implementing structured leadership development programs within the allied health workforce, empowering under-graduate practitioners through education to work effectively with uncertainty, and increasing research into the clinician experience of interdisciplinary complex care practice.